Assessment of Glutamate Transporter GLAST (EAAT1)-Deficient Mice for Phenotypes Relevant to the Negative and Executive/Cognitive Symptoms of Schizophrenia - Karlsson, Rose-Marie (2008)
Glutamatergic dysfunction is increasingly implicated in the pathophysiology of schizophrenia. Current models postulate that dysfunction of glutamate and its receptors underlie many of the symptoms in this disease. However, the mechanisms involved are not well understood. Although elucidating the role for glutamate transporters in the disease has been limited by the absence of pharmacological tools that selectively target the transporter, we recently showed that glial glutamate and aspartate transporter (GLAST; excitatory amino-acid transporter 1) mutant mice exhibit abnormalities on behavioral measures thought to model the positive symptoms of schizophrenia, some of which were rescued by treatment with either haloperidol or the mGlu2/3 agonist, LY379268 the mGlu2/3 agonist, LY379268. To further determine the role of GLAST in schizophrenia-related behaviors we tested GLAST mutant mice on a series of behavioral paradigms associated with the negative (social withdrawal, anhedonia), sensorimotor gating (prepulse inhibition of startle), and executive/cognitive (discrimination learning, extinction) symptoms of schizophrenia. GLAST knockout (KO) mice showed poor nesting behavior and abnormal sociability, whereas KO and heterozygous (HET) both demonstrated lesser preference for a novel social stimulus compared to wild-type littermate controls. GLAST KO, but not HET, had a significantly reduced acoustic startle response, but no significant deficit in prepulse inhibition of startle. GLAST KO and HET showed normal sucrose preference. In an instrumental visual discrimination task, KO showed impaired learning. By contrast, acquisition and extinction of a simple instrumental response was normal. The mGlu2/3 agonist, LY379268, failed to rescue the discrimination impairment in KO mice. These findings demonstrate that gene deletion of GLAST produces select phenotypic abnormalities related to the negative and cognitive symptoms of schizophrenia.